2019
DOI: 10.1242/dev.171397
|View full text |Cite
|
Sign up to set email alerts
|

Transient localization of the Arp2/3 complex initiates neuronal dendrite branching in vivo

Abstract: The formation of neuronal dendrite branches is fundamental for the wiring and function of the nervous system. Indeed, dendrite branching enhances the coverage of the neuron's receptive field and modulates the initial processing of incoming stimuli. Complex dendrite patterns are achieved in vivo through a dynamic process of de novo branch formation, branch extension and retraction. The first step towards branch formation is the generation of a dynamic filopodium-like branchlet. The mechanisms underlying the ini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
70
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(76 citation statements)
references
References 58 publications
6
70
0
Order By: Relevance
“…The actin cytoskeleton binds to a large array of actin-binding proteins, which regulate the structural changes in actin including polymerization and nucleation. The actin-related protein 2/3 (Arp2/3) complex is an important actin nucleator that binds to existing actin filaments and causes branching of actin filaments and neurites (Blanchoin et al, 2000;Mullins et al, 1998;Sturner et al, 2019). We hypothesized that Vcl-T-induced neurite branching is mediated by the Arp2/3 complex.…”
Section: Vcl-t-mediated Branching Phenotype Requires Arp2/3 Activity mentioning
confidence: 99%
“…The actin cytoskeleton binds to a large array of actin-binding proteins, which regulate the structural changes in actin including polymerization and nucleation. The actin-related protein 2/3 (Arp2/3) complex is an important actin nucleator that binds to existing actin filaments and causes branching of actin filaments and neurites (Blanchoin et al, 2000;Mullins et al, 1998;Sturner et al, 2019). We hypothesized that Vcl-T-induced neurite branching is mediated by the Arp2/3 complex.…”
Section: Vcl-t-mediated Branching Phenotype Requires Arp2/3 Activity mentioning
confidence: 99%
“…One study demonstrated moving actin blobs that stabilize at branch points (Nithianandam and Chien, 2018). Another study showed that the Arp2/3 complex driven nucleation of actin initiates branch formation from the F-act enriched location (Sturner et al, 2019). To test whether F-act enrichment occurs preferentially or exclusively in newly formed branches, we analyzed enrichment as a function of Strahler order.…”
Section: Bifurcations Are Strongly Associated With Local F-actin Enrimentioning
confidence: 99%
“…All motile cells, including neurons, ubiquitously employ F-actin polymerization to drive plasma membrane protrusion, and actin-filled post-synaptic filipodia are involved in synaptogenesis (Ritzenthaler et al, 2000). F-actin polymerization is rate-controlled by nucleators such as Arp2/3 complex, which binds to monomeric actin to facilitate polymerization (Konietzny et al, 2017;Sturner et al, 2019) and enables F-actin polymer branching (Smith et al, 2013), and the formin family, which acts downstream of Rho-GTPases to nucleate unbranched F-actin (Konietzny et al, 2017). In addition to their recognized role in actin nucleation and polymerization (Breitsprecher and Goode, 2013;Chesarone et al, 2010;Kawabata Galbraith and Kengaku, 2019), formins have been also implicated in microtubule stabilization through Formin Homology domain induced acetylation (Thurston et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dendrite morphology is regulated cell-intrinsically by transcription factors [4][5][6][7][8] , cytoskeletal regulators [9][10][11][12][13][14][15] , components of endocytic pathway [16][17][18] and secretory pathway 19,20 all of which have been shown to either promote or reduce dendrite branching.…”
Section: Introductionmentioning
confidence: 99%